CAREC road safety engineering manual 2 safer road works. (Asian Development Bank, 2018)
This manual explains good practices for roadwork sites, offering clear and simple guidance for CAREC road authorities to use to improve road safety at these sites for road users and workers alike. It offers information about the six-zone process, how to plan and implement a traffic management plan, and how to manage a safe worksite. This manual is essential reading for project managers, designers, supervision consultants, contractors, works supervisors and others who have a responsibility for safe worksites.